Patient reported quality of life in young adults with sarcoma receiving care at a sarcoma center - Day, Jonathan R.; Miller, Benjamin; Loeffler, Bradley T.; Mott, Sarah L.; Tanas, Munir; Curry, Melissa; Davick, Jonathan; Milhem, Mohammed; Monga, Varun (Frontiers in Psychology, 2022)
Background: Sarcomas are a diverse group of neoplasms that vary greatly in clinical presentation and responsiveness to treatment. Given the differences in the sites of involvement, rarity, and treatment modality, a multidisciplinary approach is required. Previous literature suggests patients with sarcoma suffer from poorer quality of life (QoL) especially physical and functional well-being. Adolescent and young adult (AYA) patients are an underrepresented population in cancer research and have differing factors influencing QoL. Methods: Retrospective analysis of Young Adult patients (age 18-39) enrolled in the Sarcoma Tissue Repository at University of Iowa. QoL was assessed using the self-report FACT-G questionnaire at enrollment and 12 months post-diagnosis; overall scores and the 4 well-being subscales (Physical, Emotional, Social, Functional) were calculated. Linear mixed effects models were used to measure the association between the rate of change in FACT-G subscale scores and baseline clinical, comorbidity, and treatment characteristics. Results: 49 patients were identified. 57.1% of patients had a malignancy involving an extremity. Mean FACT-G scores of overall well-being improved from baseline to 12 months (76.4 vs. 85.4, p<0.01). Social and emotional well-being did not differ significantly between baseline and 12 months. Physical well-being (18.8 vs. 23.9, p<0.01) and functional well-being (16.8 vs. 20.0, p<0.01) scores improved from baseline to 12 months. No difference was seen for FACT-G overall scores for age, sex, laterality, marital status, performance status, having children, clinical stage, limb surgery, chemotherapy, or tumor size. A difference was demonstrated in physical well-being scores for patients with baseline limitation (ECOG 1-3) compared to those with no baseline limitation (ECOG 0) (p=0.03). A difference was demonstrated in social well-being based on anatomical site (p=0.02). Conclusions: Young adults with sarcoma treated at a tertiary center had improvements in overall reported QoL at 12 months from diagnosis. Overall baseline QoL scores on FACT-G were lower than the general adult population for YA patients with sarcoma but at 12 months became in line with general population norms. The improvements seen merit further investigation to evaluate how these change over the continuum of care. Quality of life changes may be useful outcomes of interest in sarcoma trials.